Harmony and war : Confucian culture and Chinese power politics - Wang, Yuan-Kang (Contemporary Asia in the world., 2011)
This book argues that Chinese strategic culture is best described by strategic realism rather than cultural realism. By surveying the military histories of the Song and Ming dynasties, the author tries to demonstrate that Chinese governments made strategic decisions based on their relative military power with respect to their opponents. They were not influenced by "Confucian pacifism" or cultural reluctance to use force.